2015
DOI: 10.1371/journal.pone.0135040
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Workplace Heat Exposure and Controls among Occupational Hygienists and Relevant Specialists in Australia

Abstract: With warmer weather projections, workplace heat exposure is presenting a growing challenge to workers’ health and safety. Occupational hygienists are the specialist group conducting measurements and providing advice on heat stress management to industry. In order to provide insights into hygienists perceptions on workplace heat exposure, current and future preparedness for extreme heat, and barriers to possible heat adaptation strategies, a self-administered questionnaire survey was conducted during a national… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 30 publications
6
34
2
1
Order By: Relevance
“…At actual worksites, these recommendations are not always followed (Maiti, 2008;Xiang et al, 2015), and observed worktime reductions associated with increased heat exposure (Yi & Chan, 2017) are generally smaller than those of the recommendations presented herein. First, the labor capacity is calculated based on recommendations intended to prevent occupational heat-related illness.…”
Section: 1029/2018ef000883mentioning
confidence: 63%
“…At actual worksites, these recommendations are not always followed (Maiti, 2008;Xiang et al, 2015), and observed worktime reductions associated with increased heat exposure (Yi & Chan, 2017) are generally smaller than those of the recommendations presented herein. First, the labor capacity is calculated based on recommendations intended to prevent occupational heat-related illness.…”
Section: 1029/2018ef000883mentioning
confidence: 63%
“…Yet in the context of very hot ambient temperatures or chronically high WBGT, such strategies also provoke concern regarding lost productivity particularly under the substantial and ongoing increases in temperature as a result of climate change . A similar issue occurs in relation to the focus on hydration in WHS heat stress management across Australia including in the monsoon tropics . Adequate hydration contributes positively to thermoregulation.…”
Section: Part 2: Implications For the Monsoon Tropicsmentioning
confidence: 99%
“…As high levels of physical exertion are also often required to perform jobs in these industries, the insidious effects of heat stress on worker health is a persistent concern 3,4 . Other Australian occupations that lead to potentially excessive levels of heat stress include those in the military and emergency services (e.g., firefighters), who must tolerate both exogenous and endogenous sources of heat when performing high intensity physical tasks while wearing protective clothing – often coupled with exposure to high ambient temperatures 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Fluid ingestion and the avoidance of dehydration in hot workplaces is the most prominent heat stress risk mitigation strategy advised by many occupational hygienists 3 . Indeed, this notion is echoed by public health organizations during heat waves and many athletic trainers working with sportsmen/women training and competing in the heat 43,44 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation